2014
DOI: 10.1177/0892705714556829
|View full text |Cite
|
Sign up to set email alerts
|

Study of lignin dispersion in low-density polyethylene

Abstract: A maximum of 20% (w/w) lignin was used as a filler in low-density polyethylene (LDPE), together with 3-6% maleic anhydride-grafted LDPE as compatibilizer and 3-10% copper(II) sulphate pentahydrate (CuSO 4 Á5H 2 O) as lignin's dispersing agent. The resulting composites were investigated for both their mechanical properties and their melting point following the ASTM standards as well as their behaviour was compared with neat LDPE. The results reveal that addition of compatibilizer significantly improved the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Due to the hydrophilic nature of lignin, the pro-adhesive agent is obligatory, for example in polyolefin/lignin systems. In such triple component materials, a significant shift of selected mechanical properties is observed [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the hydrophilic nature of lignin, the pro-adhesive agent is obligatory, for example in polyolefin/lignin systems. In such triple component materials, a significant shift of selected mechanical properties is observed [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated of the DMA results showed that the incorporation of jute fibres into HDPE increased the modulus and stiffness of the matrix with reinforcing effect imparted by the natural fillers that allowed a higher degree of stress transfer at the interface [21][22][23]. This study aims to investigate the improvement of the thermal and mechanical characterisations of LDPE plastic reinforced corn flour (CF) as a natural additive.…”
Section: Introductionmentioning
confidence: 99%
“…This idea is not only limit to Tunisia but it can be benefiting all the countries, which present large fields oases. Furthermore, LDPE is one of the most commonly used thermoplastic to develop composites reinforced by different natural materials (cellulose, 22 lignin, 23 starch, 24 etc.). Therefore, LDPE was chosen as the model base polymer matrix to prepare date stone-filled composites.…”
Section: Introductionmentioning
confidence: 99%